RANCANG BANGUN SISTEM INFORMASI MADING DIGITAL BERBASIS WEB PADA SMK BANII SAALIM BANDAR LAMPUNG - Muhammad Ferdiansyah; Sevi Andriasari (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Wall magazine (Maiding) is a means of dissemination of information in the educational world. Despite the urgent need for fast and accurate information, today's media security is still poorly maintained, affecting the ability of students to receive information. Therefore, schools need information media and media to disseminate information quickly and accurately. Digital learning media help manage information so students receive more up-to-date information. The research methodology was carried out in three phases. In the preliminary phase, data collection was conducted through literature surveys, direct observations, and journal archives from similar surveys. The analysis phase includes a system analysis of the current bulletin board system and any bulletin boards to be created. The system development model uses the Extreme Programming Model or XP. The system is designed using the Unified Modeling Language (UML). The results of the research have led to a digital madding system that allows schools to more easily communicate information, allowing students to submit information directly through his website for Digital Wall Magazine. Meanwhile, schools can control the information coming in and decide what information is made public. Information is updated her once a week or as needed to ensure students have the most up-to-date information.